Sildenafil does not improve cardiomyopathy in Duchenne/Becker muscular dystrophy. Issue 4 (10th July 2014) - Leung, Doris G.; Herzka, Daniel A.; Thompson, W. Reid; He, Bing; Bibat, Genila; Tennekoon, Gihan; Russell, Stuart D.; Schuleri, Karl H.; Lardo, Albert C.; Kass, David A.; Thompson, Richard E.; Judge, Daniel P.; et al.
<x xml:space="preserve">Abstract</x> Objective Duchenne and Becker muscular dystrophies (DBMD) are allelic disorders caused by mutations in dystrophin. Adults with DBMD develop life‐threatening cardiomyopathy. Inhibition of phosphodiesterase 5 (PDE5) improves cardiac function in mouse models of DBMD. To determine whether the PDE5‐inhibitor sildenafil benefits human dystrophinopathy, we conducted a randomized, double‐blind, placebo‐controlled trial (ClinicalTrials.gov, number NCT01168908). Methods Adults with DBMD and cardiomyopathy (ejection fraction ≤ 50%) were randomized to receive sildenafil (20mg 3× daily) or placebo for 6 months. All subjects received an additional 6 months of open‐label sildenafil. The primary endpoint was change in left ventricular end‐systolic volume (LVESV) on cardiac magnetic resonance imaging. Secondary cardiac endpoints, skeletal muscle function, and quality of life were also assessed. Results An interim analysis (performed after 15 subjects completed the blinded phase) revealed that 29% (4 of 14) of subjects had a ≥10% increase in LVESV after 6 months of sildenafil compared to 13% (1 of 8) of subjects receiving placebo. Subjects with LVESV > 120ml at baseline were more likely to worsen at 12 months regardless of treatment assignment (p = 0.035). Due to the higher number of subjects worsening on sildenafil, the data and safety monitoring board recommended early termination of the study. There were no statistically significant differences in outcome measures between treatment arms. Interpretation Due to the small sample size, comparisons between groups must be interpreted with caution. However, this trial suggests that sildenafil is unlikely to improve cardiac function in adults with DBMD. Ann Neurol 2014;76:541–549